3He/4He Signature of Magmatic Fluids from Telica (Nicaragua) and Baru (Panama) Volcanoes, Central American Volcanic Arc - Andrea L. Rizzo; Philippe Robidoux; Alessandro Aiuppa; Andrea Di Piazza (Applied Sciences, 2022)
Constraining the magmatic 3He/4He signature of fluids degassed from a magmatic system is crucial for making inferences on its mantle source. This is especially important in arc volcanism, where variations in the composition of the wedge potentially induced by slab sediment fluids must be distinguished from the effects of magma differentiation, degassing, and crustal contamination. The study of fluid inclusions (FIs) trapped in minerals of volcanic rocks is becoming an increasingly used methodology in geochemical studies that integrates the classical study of volcanic and geothermal fluids. Here, we report on the first noble gas (He, Ne, Ar) concentrations and isotopic ratios of FI in olivine (Ol) and pyroxene (Px) crystals separated from eruptive products of the Telica and Baru volcanoes, belonging to the Nicaraguan and Panamanian arc-segments of Central America Volcanic arc (CAVA). FIs from Telica yield air corrected 3He/4He (Rc/Ra) of 7.2–7.4 Ra in Ol and 6.1–7.3 in Px, while those from Baru give 7.1–8.0 Ra in Ol and 4.2–5.8 Ra in Px. After a data quality check and a comparison with previous 3He/4He measurements carried out on the same volcanoes and along CAVA, we constrained a magmatic Rc/Ra signature of 7.5 Ra for Telica and of 8.0 Ra for Baru, both within the MORB range (8 ± 1 Ra). These 3He/4He differences also reflect variations in the respective arc-segments, which cannot be explained by radiogenic 4He addition due to variable crust thickness, as the mantle beneath Nicaragua and Panama is at about 35 and 30 km, respectively. We instead highlight that the lowest 3He/4He signature observed in the Nicaraguan arc segment reflects a contamination of the underlying wedge by slab sediment fluids. Rc/Ra values up to 9.0 Ra are found at Pacaya volcano in Guatemala, where the crust is 45 km thick, while a 3He/4He signature of about 8.0 Ra was measured at Turrialba volcano in Costa Rica, which is similar to that of Baru, and reflects possible influence of slab melting, triggered by a change in subduction conditions and the contemporary subduction of the Galapagos hot-spot track below southern Costa Rica and western Panama.